Hagios Charalambos : A Minoan Burial Cave in Crete - Betancourt, Philip P. (Prehistory Monographs, 2014)
This is the first of five planned volumes to present the primary archaeological report about the excavation of the cave of Hagios Charalambos in eastern Crete. The Minoans used this small cavern as an ossuary for the secondary burial of human remains and grave goods, primarily during the Early and Middle Bronze Age. The geography and geology surrounding the cave is discussed along with the methodology of the excavation. A portion of the pottery and all of the small finds are presented with many illustrations